Increasing Economic Empowerment of the People through Productive Waqf - Aripin Marpaung (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2020)
Post-press freedom in Indonesia (the passing of Law No. 40/1999) gave rise to a variety of new problems, ranging from widespread violations of the Journalistic Code of Ethics (KEJ) to violence against journalists. In fact, the Press Law No. 40/1999 was actually born to provide fresh air for press freedom in the country and to provide the widest possible space for press operations that were previously locked in the shackles of power. The results of the discussion found that violations of the journalistic code of ethics tended to be committed by young journalists who were still raw with the articles of the code of ethics and the Press Law No. 40/1999. Forms of violation are sometimes reluctant to confirm sources, using fictitious anonymous sources, do not keep the identity of victims of immoral crimes secret, use bar language, and tend to attack individual privacy, and harass SARA - things that were previously very sacred. The results of the study prove that between press freedom and violations of journalistic code of ethics and violence against journalists have a significant relationship, while violations of journalistic codes of ethics with violence against journalists also have a significant relationship, but between press freedom and violence against journalists have a relative relationship during the conflict. Aceh does not have a causal relationship, but after the peace of GAM Aceh - RI there is a very significant relationship, in fact it was carried out by former fighting elements in Aceh GAM and the TNI / Polri. To avoid continuing victims, journalists in Indonesia, especially Aceh is expected to be able to apply the Proportional and Professional Concept (2P); Professional as a basic competency in journalistic and proportional operations is a provision to face various threats and dangers in fieldo perations.